Measurement of the ηc(1S) production cross-section in pp collisions at √s =13 TeV; The European Physical Journal C; Vol. 80, iss. 3 - Aaij R. Roel; Beteta C. B. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2020, 2020)
Title screen